Peran Lembaga Baznas Dalam Meningkatkan Kesejahteraan Masyarakat Kabupaten Pekalongan - Minhatis Sa’adah; Rifqi Hidayatullah; Dwi Septyani (MES Management Journal, 2022)
This study describes the role of the National Development Planning Agency in improving the welfare of the people of Pekalongan Regency. The research method used is a qualitative method. The data sources used are primary data sources and secondary data sources. Data were collected by observation, interview, and documentation methods. The results of this study found that BAZNAS in Pekalongan has an important role for the community such as providing educational scholarships for semester 5 and 6 students who come from underprivileged families, providing assistance to flood victims in the form of money, food, clothing, health, and medicines. medicine. BAZNAS Pekalongan collects zakat in various ways, such as coming directly to the Baznas office, post, bank, and so on. BAZNAS Pekalongan also innovates in collecting zakat funds through the Muzaki Card to make it easier and more transparent. The collected zakat is then used to help improve the welfare of the community in various fields. So, with the management and distribution of zakat funds through several programs and services that are carried out effectively and optimally, it can help the community in improving welfare. Keywords: Zakat; BAZNAS; Well-being